2018
DOI: 10.1007/s12253-018-0558-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of TRIM 28 in Squamous Carcinoma of Esophagus

Abstract: Tripartite motif-containing protein 28 (TRIM28) has been proved to accelerate cell proliferation and metastasis in a variety of human cancers. However, the role of TRIM28 in esophageal squamous cell carcinoma (ESCC) remains unclear. In this study, to compare the biological effect and significance of TRIM28 expression in ESCC, immunohistochemistry (streptavidin-perosidase, S-P) method was used firstly to examine the expression of TRIM28 in 136 cases of ESCC, 35 cases of high grade intraepithelial neoplasia (HGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Immunohistochemistry was conducted using bone marrow tissue sections following previously described methods [ 32 ]. Bone marrow biopsy sections were fixed with formalin, embedded in paraffin, and cut into 4-μm-thick sections.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was conducted using bone marrow tissue sections following previously described methods [ 32 ]. Bone marrow biopsy sections were fixed with formalin, embedded in paraffin, and cut into 4-μm-thick sections.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to their normal counterparts, cervical cancer cell lines and tissues also show an upregulated expression of TRIM28 transcriptional co-activator. 418 TRIM28 has been found to significantly increase the phosphorylation of mTOR and its downstream molecule S6K1, leading to mTOR mediated cervical cancer growth and progression. 419 …”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%
“…Studies have shown that the human tripartite motif (TRIM) protein family can not only maintain the normal physiological function of the body, but also participate in the regulatory process of a variety of disease pathogenesis, including viral infection, tumorigenesis, neurodegeneration and other diseases (Czerwińska et al 2017;Liu et al 2019). TRIM28 is a large molecular protein with multiple domains and is a member of TRIM protein family.…”
Section: Introductionmentioning
confidence: 99%